Arguing with Arguments: Argument Quality, Argumentative Norms, and the Strengths of the Epistemic Theory - Siegel, Harvey (Informal Logic)

(untitled) (Informal Logic, 2023)
‘Argument’ has multiple meanings and referents in contemporary argumentation theory. Theorists are well aware of this but often fail to acknowledge it in their theories. In what follows, I distinguish several senses of ‘argument’ and argue that some highly visible theories are largely correct about some senses of the term but not others. In doing so, I hope to show that apparent theoretical rivals are better seen as collaborators or partners, rather than rivals, in the multi-disciplinary effort to understand ‘argument,’ arguments, and argumentation in all their varieties. I argue as well for a pluralistic approach to argument evaluation and argumentative norms, since arguments and argumentation can be legitimately evaluated along several dimensions, but urge that epistemic norms enjoy conceptual priority.